Deciphering spatially confined immune evasion niches in osteosarcoma with 3-D spatial transcriptomics: a literature review - Qiu, Guangqiang; Tang, Yongcheng; Zuo, Junhui; Wu, Heng; Wan, Yongxian (Frontiers in Oncology, 2025)
Osteosarcoma (OS) is the most common primary malignant bone tumour of childhood, yet five-year survival has plateaued at ~60–70% for localised disease and plunges below 30% once metastasis emerges. Formerly viewed as a cell-intrinsic neoplasm entombed in mineralised bone, OS is now understood as a spatially stratified ecosystem whose immune-evasion niches choreograph progression. Three-dimensional spatial transcriptomics (3-D ST) fuses barcode-based transcript capture with volumetric reconstruction, preserving x-, y- and z-axis context and exposing concentric C1QC necrotic belts, MCAM (melanoma cell-adhesion molecule, CD146) peri-vascular corridors, hypoxic glycolytic rims and therapy-induced tertiary-lymphoid islets that collectively sequester cytotoxic lymphocytes. Pre-clinical atlases link PD-L1 high SOX9 stem-like cells, LGALS3 macrophages and VEGFA-driven endothelial tips to chemoresistance and immune-checkpoint failure, while ligand–receptor inference highlights VEGFA–VEGFR2, CXCL12–CXCR4 and complement–CSF1R axes as actionable bottlenecks. Translational efforts already echo these insights: dual MCAM/VEGFR blockade collapses vascular gates, C1s or CSF1R antagonists dismantle necrotic-core “cold pockets”, and MCT1–POSTN combinations target lactate-stiffened stromal shells. By weaving methodological advances with emergent biology, this review crystallises how 3-D ST redefines OS immunopathology, sharpens biomarker discovery and accelerates spatially guided combination therapies. We aim to expose diagnostic blind spots, spotlight niche-directed interventions and chart a roadmap toward lifting the long-standing therapeutic ceiling in osteosarcoma.